Ethnobotanical Study of Plant in Historical-Religious Tourism Area and the Sacred Place at Sumenep, Madura - Eva Kristinawati Putri; Ahmad Bashri (University of Brawijaya, 2019)
An ethnobotanical study in the Sumenep regency of Madura island has been carried out by observing nine locations, including the historical-religious tourism area and sacred places. This article described plant diversity, use value associated with local knowledge, and socio-cultural value associated with local wisdom. Totally 35 respondents were interviewed consist of primary respondents from each research area and typical respondents. Totally 31 plant species were found in study sites, covering cultivated and socio-cultural plants. Plant diversity was related to role of the location where they took place. Sumenep Palace, the main tourism area located in the center of town, reached the highest diversity of two socio-cultural and 18 cultivated plants as its domestication efforts to attract visitors. Ficus benjamina had the highest socio-cultural values as a usual dwelling for spirits and used to place some offerings, accelerate fortune and specific occasions. The local wisdom of Sumenep people directly related to how these plants can provide benefits, such as Manilkara kauki and Morinda citrifolia which were valuable as socio-cultural plants and fruit trees at once. Ficus benjamina which were valuable as socio-cultural plants related to local wisdom indirectly.